Knockdown of CYP6SZ3 and CYP6AEL1 genes increases the susceptibility of Lasioderma serricorne to ethyl formate and benzothiazole - Li, Xiaokun; Ma, Lixin; Yang, Wenjia; Xu, Kangkang (Frontiers in Physiology, 2024)
Insect cytochrome P450 monooxygenases (CYPs) play crucial roles in the metabolic detoxification of insecticides. Ethyl formate and benzothiazole have recently regained popularity as fumigants due to rising resistance to phosphine in the stored-product pests. However, the mechanisms underlying tolerance to these two fumigants in Lasioderma serricorne, a major global insect pest of stored products, remain poorly understood. In this study, two CYP genes, named CYP6SZ3 and CYP6AEL1, were identified from L. serricorne, belonging to the CYP6 family and containing five conserved domains characteristic of CYP proteins. Spatiotemporal expression analysis revealed that both genes were predominantly expressed in the larval stage and showed the highest expression in the foregut. Upon exposure to ethyl formate and benzothiazole, both genes were upregulated, with significantly increased transcription levels following treatment. RNA interference-mediated silencing of CYP6SZ3 and CYP6AEL1 led to increased susceptibility and significantly higher mortality of L. serricorne when exposed to these fumigants. Homology modeling and molecular docking analyses showed stable binding of these fumigants to CYP6SZ3 and CYP6AEL1 proteins, with binding free energies from −26.88 to −94.68 kcal mol−1. These findings suggest that the induction of CYP6SZ3 and CYP6AEL1 is likely involved in the detoxification of ethyl formate and benzothiazole in L. serricorne.